INVESTIGATE THE EFFECT OF DIFFERENT DESIGN PARAMETER ON PERFORMANCE EVALUATION OF STRAIGHT BLADEVERTICAL AXIS WIND TURBINE (SB-VAWT) - Khammas, Farhan; M.T., Mustaffa; U, Ryspek; Askar, Kadhim; Qasimr, Ahmed; Quadir, Ghulam (International Journal of Engineering Technologies and Management Research, 2015)
Energy is an essential ingredient for socioeconomic development and economic growth country. Energy is available in two different forms, fast depleting or non-renewable (coal, fuel, natural gas) and renewable (solar, wind, hydro etc.). In fact, one of the biggest sources of energy is all around us all of the time, the wind. Every year the number of installed wind power plants in the world increases. Vertical axis wind turbines (VAWT) are capable of producing a lot of power, and offer many advantages for small-scale and domestic applications. One drawback of Darrieus Type VAWT is their inability to reliably self-start at a low tip speed ratio [1]. The main purpose of the study described here is to investigate the effect of different design parameter on performance evaluation of SB-VAWTs.